FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STIGMA TENAGA KESEHATAN TERHADAP ORANG DENGAN HIV/AIDS DI RSUD MGR. GABRIEL MANEK,SVD ATAMBUA 2022 - Ulyartha Tampubolon; Imelda Februati Ester Manurung; Ribka Limbu (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
The HIV control strategy carried out in Indonesia in 2020-2024 is to create a supportive environment for key populations of HIV and PLWHA to improve the quality of life of PLWHA. One of the factors that hinders access, availability and utilization of HIV testing and care services is HIV stigma. Stigma is not only carried out by the general public, but also by health workers. This study aims to identify factors associated with prejudice among health care workers against people living with HIV. This type of study is a cross-sectional investigation that considers quantitatively. The location of the study was carried out at the Mgr. Gabriel Manek, SVD Atambua, Belu Regency, which was held in September 2022. The population of this study was 429 health workers with a total of 203 respondents. The sample technique used is simple random sampling and the data analysis technique used is the chi-square test with a significance level of =0.05. This study resulted that there was a significant relationship between knowledge, perception and stigma against PLWHA and also no relationship between length of work, information exposure and interaction with PLWHA with stigma against PLWHA. The suggestion of this research is that health workers must increase their understanding and increase information about HIV and AIDS so that there is no stigma against PLWHA